Stability and Ultimate Load of Three-Layered Plates – A Parametric Study - Grądzki, R.; Kowal-Michalska, K. (Engineering Transactions, 2003)
This work deals with the analysis of influence of some geometrical and material parameters of layers on the mass, critical stress and ultimate load of three-layered plates. The plates are built of metal outer layers and a composite core. To obtain the maximum load value, the analysis is carried out in the elasto-plastic range basing on the Tsai-Wu criterion and Prandtl-Reuss equations. The solution is obtained by an analytical-numerical method.